2021
DOI: 10.31744/einstein_journal/2021ao6000
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional study on the effects of passive smoking in kidneys of rats

Abstract: Objective To analyze whether passive inhalation of cigarette smoke causes morphological, structural, and functional changes in kidneys of rats. Methods Wistar rats, aged eight weeks, weighing on average 260g, were divided into Control Group and Smoking Group. Each group was subdivided into four groups of ten animals for morphofunctional analysis, in a period of seven and 28 days. The Smoking Group was exposed to smoke of 40 cigarettes per day, at certain times and in au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…In addition, recent studies have shown that side-stream smoke, which is the main component of passive smoke, contains more toxic substances than those found in mainstream smoke, suggesting that passive smoking exposure can also cause serious effects. 26 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have shown that side-stream smoke, which is the main component of passive smoke, contains more toxic substances than those found in mainstream smoke, suggesting that passive smoking exposure can also cause serious effects. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Feed and water intake were monitored throughout the experimental period. (9) Adaptation of SG rats to cigarette smoke was achieved by gradual exposure to burning cigarettes. Rats were exposed in pairs to the smoke of up to 40 cigarettes per day (high yield; tar: 10mg; nicotine: 0.8mg; carbon monoxide: 10mg) for 7 to 28 days.…”
Section: Methodsmentioning
confidence: 99%
“…Carbon dioxide was measured in CG and SG rat boxes and housing environment using a calibrated carbon dioxide meter (AZ Instruments, model AZ 77535, serial number 10109975) (certificate 00948/2016). (9) Source: Moraes CA, Breda-Stella M, Carvalho CA. Morphofunctional study on the effects of passive smoking in kidneys of rats.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations